Adding Twitter‐specific features to stylistic features for classifying tweets by user type and number of retweets. (22nd January 2014) - Arakawa, Yui; Kameda, Akihiro; Aizawa, Akiko; Suzuki, Takafumi
<x xml:space="preserve">Abstract</x> Recently, Twitter has received much attention, both from the general public and researchers, as a new method of transmitting information. Among others, the number of retweets (RTs) and user types are the two important items of analysis for understanding the transmission of information on Twitter. To analyze this point, we applied text classification and feature extraction experiments using random forests machine learning with conventional stylistic and Twitter‐specific features. We first collected tweets from 40 accounts with a high number of followers and created tweet texts from 28, 756 tweets. We then conducted 15 types of classification experiments using a variety of combinations of features such as function words, speech terms, Twitter's descriptive grammar, and information roles. We deliberately observed the effects of features for classification performance. The results indicated that class classification per user indicated the best performance. Furthermore, we observed that certain features had a greater impact on classification. In the case of the experiments that assessed the level of RT quantity, information roles had an impact. In the case of user experiments, important features, such as the honorific postpositional particle and auxiliary verbs, such as "desu" and "masu, " had an impact. This research clarifies the features that are useful for categorizing tweets according to the number of RTs and user types.